Biochemical characterization of an acidophilic β-mannanase from Gloeophyllum trabeum CBS900.73 with significant transglycosylation activity and feed digesting ability. (15th April 2016) - Wang, Caihong; Zhang, Jiankang; Wang, Yuan; Niu, Canfang; Ma, Rui; Wang, Yaru; Bai, Yingguo; Luo, Huiying; Yao, Bin
Highlights: G. trabeum Man5A produced in P. pastoris was acidophilic with the pH optimum of 2.5. The enzyme showed excellent stability over the broad pH range of 2.0–10.0. It exhibited a high specific activity (1356 U/mg) in a four-site binding mode. It possessed both mannan-degrading activity and transglycosylation activity. It was resistant to pepsin and trypsin and degraded corn–soybean meal effectively. Abstract: Acidophilic β-mannanases have been attracting much attention due to their excellent activity under extreme acidic conditions and significant industrial applications. In this study, a β-mannanase gene of glycoside hydrolase family 5, man5A, was cloned from Gloeophyllum trabeum CBS900.73, and successfully expressed in Pichia pastoris . Purified recombinant Man5A was acidophilic with a pH optimum of 2.5 and exhibited great pH adaptability and stability (>80% activity over pH 2.0–6.0 and pH 2.0–10.0, respectively). It had a high specific activity (1356 U/mg) against locust bean gum, was able to degrade galactomannan and glucomannan in a classical four-site binding mode, and catalyzed the transglycosylation of mannotetrose to mannooligosaccharides with higher degree of polymerization. Besides, it had great resistance to pepsin and trypsin and digested corn–soybean meal based diet in a comparable way with a commercial β-mannanase under the simulated gastrointestinal conditions of pigs. This acidophilic β-mannanase represents a valuable candidate for wide use in various industries, especially in the feed.